1982
DOI: 10.1144/gsjgs.139.6.0721
|View full text |Cite
|
Sign up to set email alerts
|

Late Mesozoic sedimentation in the northern Antarctic Peninsula and its relationship to the southern Andes

Abstract: Two distinct phases of island-are evolution are recognized in late Mesozoic sedimentary rocks of the northern Antarctic Peninsula. During late Jurassic (Kimmeridgian-Tithonian) times, alternating radiolaria-rich mudstones and ash-fall tuffs were deposited under shallow marine euxinic conditions in association with restricted volcanic centres. The name Nordenskjöld Formation is proposed for this lithostratigraphic unit. Subsequently, during the early Cretaceous, a major episode of volcanism and uplift led to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 19 publications
1
33
0
1
Order By: Relevance
“…Aitkenhead (1975) regarded the latter as the youngest member of the volcanic succession on Trinity Peninsula. In conjunction with the revized sedimentary stratigraphy at Longing Gap, NE of Larsen Inlet (Farquharson 1982), it is suggested that arc-building activity in this area reached a climax in Lower Cretaceous times. The chief evidence for Jurassic magmatism rests with K-Ar ages of 158-169 Ma for the plutonic complex round Mount…”
Section: Trinity Peninsulamentioning
confidence: 94%
“…Aitkenhead (1975) regarded the latter as the youngest member of the volcanic succession on Trinity Peninsula. In conjunction with the revized sedimentary stratigraphy at Longing Gap, NE of Larsen Inlet (Farquharson 1982), it is suggested that arc-building activity in this area reached a climax in Lower Cretaceous times. The chief evidence for Jurassic magmatism rests with K-Ar ages of 158-169 Ma for the plutonic complex round Mount…”
Section: Trinity Peninsulamentioning
confidence: 94%
“…The geology of eastern Graham Land has been closely correlated with the successions of Patagonia from the Ordovician at the time of the Famatinian arc (Riley et al 2012b) to at least the Middle Jurassic during the extensive felsic volcanism associated with the Chon Aike silicic large igneous province and subsequently from the Late Jurassic to the Early Cretaceous (Farquharson 1982).…”
Section: The Eastern Domainmentioning
confidence: 99%
“…Cretaceous to Paleogene strata accumulated during thermal subsidence of the basin (Hathway, 2000), with sediment being shed from the Antarctic Peninsula to the west as indicated by palaeocurrent directions and provenance studies (Farquharson, 1982;Ineson, 1989;Pirrie, 1991). Wood is abundant within these marine sequences and is considered to have been derived from the treeforming elements of the vegetation from the Antarctic Peninsula.…”
Section: Geological Setting and Palaeoenvironmentmentioning
confidence: 99%